Caring for those who care: design and implementation of a multi-level and multi-component program for psychosocial support and mental health care of health workers during the COVID-19 pandemic - Gomez P., Victor; Martinic J., Mirko; López G., Cristian; Prieto S., Ricardo; Flores L., Catalina; Ibañez , Carlos; Barroilhet D., Sergio (Revista de Psiquiatría Clínica, 2022)
The COVID 19 pandemic has brought social, economic, and health consequences around the world. Health workers are not only more exposed to contagion, but also to multiple emotional stressors and greater needs related to the care of their mental health. It is essential to develop strategies to ensure the well-being of health workers, which will have a relevant impact on the ability to respond to the health crisis. Method: An intervention strategy developed in the Clinical Hospital of the University of Chile, the Emotional Health Support Program, formulated from the review of updated literature and experiences of other institutions, is presented and discussed. Results: A program composed of five levels of intervention aiming to detect and attend to needs related to mental health at different levels of complexity in an individual and group basis was formulated . Discussion: There is evidence that supports the need for care for specific groups in this pandemic, including health workers. The PASE program is a feasible intervention to support the health workers who are on the frontline of action in the COVID-19 pandemic.